Illusions of Victory - Grant Marthinsen (International Institute of Islamic Thought, 2018)
In late 2006 and then 2007 the Sunni Arab tribes in the Anbar province, located in western Iraq, came together with the United States armed forces positioned in the same province and conducted a grueling fight against Al-Qaeda in Iraq, also known at the time as the Islamic State in Iraq (ISI, as it shall be referred to hereafter). Their victory in this struggle has since been held up as a shining example of counterinsurgency tactics, even if, as author Carter Malkasian points out, the specific reasons that the movement succeeded have been oversimplified and misidentified in accounts rendered since the Awakening. After the brutal advance of the Islamic State in Iraq a few years ago, however, the image of Anbar as a counterinsurgency example has been the target of no small amount of doubt. Malkasian argues that Anbar should be remembered not as an example of a successful counterinsurgency strategy but instead as a warning to not engage in military interventions without a better understanding of the local dynamics and politics of a given country or wider region, nor without the willingness to commit one’s forces for a much longer period than the US initially did in Iraq ...